Bitcoin and stone money: Anglophone use of Yapese economic cultures, 1910-2020 - Jo Lindsay Walton (Finance and Society, 2022)
Recently parallels have been drawn between Bitcoin and Yapese stone money. This article focuses on Fitzpatrick and McKeon's (2019) exploration of similarities and differences. The analogy between Bitcoin and Yapese stone money is based on proposed commonalities that are inaccurate, ill-defined, and/or trivial. However, this does not signal a need to refine the comparison, but rather a need to reconsider the rationale for attempting it in the first place. Recent attempts to redefine Yapese stone money using terminology from the field of cryptocurrency reproduces a longer textual history in which writers from the Global North have misrepresented Yap for pedagogic or polemic convenience. Examples include works by William Furness III, John Maynard Keynes, Milton Friedman, and influential macroeconomics textbooks, such as N. Gregory Mankiw's Macroeconomics. This history features frequent colonialist tropes of Yap as well as the erasure of histories of colonial violence and power. More caution should be exercised in the study and pedagogic use of Yapese economic cultures, and greater effort should be made to center Yapese voices, acknowledge colonial contexts, and reflect positionality and uncertainty.
Keywords: 300; Bitcoin; blockchain; macroeconomics; money; social currency; Yap